Schizophrenia Plays a Negative Role in the Pathological Development of Myocardial Infarction at Multiple Biological Levels - Yang, Xiaorong; Chen, Yao; Wang, Huiyao; Fu, Xia; Kural, Kamil Can; Cao, Hongbao; Li, Ying (Frontiers in Genetics, 2021)
It has showed that schizophrenia (SCZ) is associated with a higher chance of myocardial infarction (MI) and increased mortality. However, the underlying mechanism is largely unknown. Here, we first explored the literature-based genetic pathway linking SCZ and MI and tested the expression levels of the genes by a meta-analysis involved using nine gene expression datasets of MI. In addition, a literature-based data mining process was conducted to explore the connection between SCZ at different levels: small molecules, complex molecules, and functional classes. The genetic pathway revealed nine genes connecting SCZ and MI. Specifically, SCZ activates two promoters of MI (IL6 and CRP) and deactivates seven inhibitors of MI (ADIPOQ, SOD2, TXN, NGF, ADORA1, NOS1, and CTNNB1), suggesting that no protective role of SCZ in MI was detected. Meta-analysis showed that one promoter of MI (CRP) presented no significant increase, and six out of seven genetic inhibitors of MI demonstrated minor to moderately increased expression (). Therefore, the elevation of CRP and inhibition of the six inhibitors of MI by SCZ could be critical pathways to promote MI. Nine regulators of MI were influenced by SCZ, including two gene families (inflammatory cytokine and IL1 family), five small molecules (lipid peroxide, superoxide, ATP, ascorbic acid, melatonin, arachidonic acid), and two complexes (CaM kinase 2 and IL23) have been identified. Our results suggested that SCZ promotes the development and progression of MI at different levels, including genes, small molecules, complex molecules, and functional classes.